If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=(y-3)-8y
We move all terms to the left:
11-((y-3)-8y)=0
We calculate terms in parentheses: -((y-3)-8y), so:We get rid of parentheses
(y-3)-8y
We add all the numbers together, and all the variables
-8y+(y-3)
We get rid of parentheses
-8y+y-3
We add all the numbers together, and all the variables
-7y-3
Back to the equation:
-(-7y-3)
7y+3+11=0
We add all the numbers together, and all the variables
7y+14=0
We move all terms containing y to the left, all other terms to the right
7y=-14
y=-14/7
y=-2
| 1/2(b+2)+3b=–1 | | 4x-9=3.5x=9 | | -2=x+4.5-x | | w+(2w-3)=30 | | 3(2r+3)=69 | | -4.8x=1 | | 5/9x-8=-23 | | 8z-8=6z+8 | | 11y+14+56=180 | | 3(x−2)−9x=−2(3x+3) | | 4k+5+66=180 | | 5(2t–4)=10t | | 5-2(3x+5)=10x-3 | | 9h+1=7+10h | | 7x+30=3 | | 12+2p+11=22+2p | | x+14+8x-10=160 | | 10+3k=12 | | 15-5w=20 | | 4x°+(3x+2)°=90° | | s+1=8 | | 21+5h-7h=56 | | -9k+3=7-7k | | 15.35-3.8x=-26.75+2.2x | | -6(b+3)=-8+5 | | 8(x+1)=3x-2 | | 79+u=75 | | 3x+4+6x=13 | | 7.26+x=16.82 | | 9x+2x(x-3)=30 | | 4(2+4g)=12g | | -15-2y=-12+4y |